Peran Pemerintah Desa Dalam Pembangunan Infrastruktur di Desa Bubode Kecamatan Tomilito Kabupaten Gorontalo Utara - Kasim, Maqfira A.; Ilato, Rosman; Nani, Yacob Noho (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine the role of the Village Government in Infrastructure Development in Bubode Village, Tomilito District, North Gorontalo Regency as seen from the dimensions of (1) Regulator, (2) Dynamisator, (3) Facilitator. The research method used is qualitative with descriptive research type. Data collection was carried out by observation, interviews and documentation. The results of this research show that the Government's role in infrastructure development is good. In terms of (1) Regulators, the village government and the community jointly determine policies to ensure that development will be implemented in accordance with community expectations. (2) Dynamisator, the village government can encourage the community to actively participate in development so that it can run the wheels of government. (3) Facilitator, it cannot be said that it has not been implemented well because infrastructure development still experiences several obstacles in maintaining development such as village roads, bridges and livable houses.